Focus Group Discussion Penerapan Bioteknologi dalam Budidaya Ikan sebagai Upaya Peningkatan Produktivitas Perikanan di Kecamatan Anjongan, Kabupaten Mempawah: Focus Group Discussion Application of Biotechnology in Fish Cultivation as a Way to Increase Fishery Productivity in Anjongan District, Mempawah Regency - Pratama, Sandi Fransisco; Khairillah, Yuyun Nisaul; Pasmawati, Pasmawati; Fitriagustiani, Fitriagustiani; Alang, Hasria; Pratama, Kharisma (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
BPS data for Mempawah Regency shows that aquaculture production in the Anjongan District is 163 tons/year. This production result is still lower compared to other sub-districts. One of the factors causing the not-yet-optimal effects of aquaculture production in the Anjongan District is the limited mastery of aquaculture technology. Biotechnology in the field of fisheries offers sustainable technology to increase fishery resources. This Community Service aims to conduct a Focus Group Discussion on plans to apply biotechnology in fish farming. In this activity, several applications of biotechnology in aquaculture were presented. The results of the discussion activities revealed several problems, including limited sources of clean water for fish farming, high costs for feed, and limited resources for implementation in the field of biotechnology. Feed is a top priority and an essential factor because fish can grow in a healthy, optimal, and quality manner.